UMP, Malaysian Highway Authority (LLM) work together in highway research and education - Norhidayah, Mohamad (2018)
Kuala Lumpur, 8 March – University Malaysia Pahang closed a deal with Malaysian Highway Authority (LLM) as its new strategic partner. In this latest partnership, the scope will be on education and research, focusing more on highway engineering, traffic management and infrastructure management that will benefit the user as a whole.